Social Support and Future Optimism of Adolescent at Salatiga Islamic Orphanage - I’anatul Khasanah; Nanik Prihartanti; Marwanto Marwanto (Fakulatas Dakwah IAIN Salatiga, 2020)
AbstractGenerally, teenagers in an orphanage have had problems with their environment,friends, and society. So that they have low optimism in facing their future. This study aims to determine whether there is a relationship between social support and optimism for the future of adolescents in the Salatiga Islamic orphanage. The research subjects were adolescents at the Salatiga Islamic orphanage who were taken using a purposive sampling technique with a total of 120 subjects, consisting of 52.5% boys and 47.5% girls. The data was collected using a social support scale and a future optimism scale. Data analysis was processed using statistical regression analysis techniques. The analysis showed a significant positive relationship between social support and optimism for the future of adolescents in the orphanage. Abstrak Remaja di panti asuhan pada umumnya pernah mempunyai masalah terhadaplingkungannya, teman, dan masyarakat. Sehingga mempunyai optimisme yangrendah dalam menghadapi masa depannya. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan antara dukungan sosial dan optimisme masadepan remaja di panti asuhan Islam Salatiga. Subyek penelitian adalah remajadi panti asuhan Islam Salatiga yang diambil dengan menggunakan teknikpurposive sampling dengan jumlah subjek 120 orang, terdiri atas 52,5% remajalaki-laki dan 47,5% remaja perempuan. Pengumpulan data dilakukan denganmenggunakan skala dukungan social dan skala optimisme masa depan. Analisisdata diolah dengan teknik statistik analisis regresi. Hasil analisis menunjukkanhubungan positif signifikan antara dukungan sosial dan optimism masa depanremaja di panti asuhan.